Penerapan Metode Gerak dan Lagu untuk Meningkatkan Minat Belajar Anak di RA Kebunsari Plakpak Pamekasan - Siti Maryam; Shohebul Hajad (STAI Al Mujtama Pamekasan, 2025)
This study aims to determine how the movement and song method can be applied to increase learning interest in early childhood. Using qualitative research methods, data were obtained through observations and interviews. The results indicate that the implementation of the movement and song method at RA Kebunsari Plakpak consists of three stages: preparation, core, and evaluation. The movement and song method applied can stimulate learning interest in children aged 5-6 years, including aspects of flexibility, coordination, and movement accuracy, which show very good development. The researchers demonstrated that movement and song activities are a strategy that can be used to increase children's learning interest.